2024
DOI: 10.3390/plants13071043
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Phytoprofiling of Achillea millefolium Morphotypes: Assessing Antioxidant Activity, Phenolic and Triterpenic Compounds Variation across Different Plant Parts

Lina Raudone,
Gabriele Vilkickyte,
Mindaugas Marksa
et al.

Abstract: Achillea millefolium L., commonly known as yarrow, is a versatile and widely distributed plant species with a rich history of ethnopharmacological significance. This study aimed to evaluate the comparative differences of A. millefolium inflorescence morphotypes. The phytochemical profile of white and pink inflorescence morphotypes was characterised by a complex of thirty-four phenolic and triterpene compounds. The species has distinct morphotypes of white and pink inflorescence. Phenolic and triterpenic profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…These investigators identified five chemotypes: 1,8cineole/(E)-nerolidol, high cubenol, high germacrene-D/isospathulenol, high camphor/cubenol, and high 1,8-cineole/ β-thujone/cubenol. Furthermore, Raudone and co-workers investigated different morphotypes of A. millefoium and found notable differences in triterpenoid and phenolic components [2]. The A. millefolium essential oils were analyzed by enantioselective GC-MS (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These investigators identified five chemotypes: 1,8cineole/(E)-nerolidol, high cubenol, high germacrene-D/isospathulenol, high camphor/cubenol, and high 1,8-cineole/ β-thujone/cubenol. Furthermore, Raudone and co-workers investigated different morphotypes of A. millefoium and found notable differences in triterpenoid and phenolic components [2]. The A. millefolium essential oils were analyzed by enantioselective GC-MS (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Achillea millefolium L. (Asteraceae) is a polymorphous species with a complex taxonomy [1,2]. World Flora Online currently lists 161 synonyms for the species [3].…”
Section: Introductionmentioning
confidence: 99%
“…Native American nations used the plant for healing cuts and abrasions, for relief of earaches and throat infections, and as an eyewash. Common yarrow was used by plains Indigenous peoples to reduce pain or fever and aid sleep ( Table 1 ) [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%